Influencia del ozonotroposférico en la capacidad de captación de co2 en ocimum tenuiflorum - Quishpe Quishpe, Luis Miguel (2017)
The deterioration of air quality is increasing as the year is progress. Concentrations of primary pollutants VOCs, sulfur oxides, carbon and nitrogen are increasing due to industrial development and the continued use of fossil fuels. The quantities of tropospheric ozone (O3) in the same way have grown, since this is formed through the photolysis of the already mentioned primary contaminants. The present study analyzes the influence of O3 on the uptake of CO2. From the exposure of plants of the same species Ocimum tenuiflorum, at different concentrations of O3: T.1: Treatment 1, ambient concentration, T.2: Treatment 2.40 microgram / m3 and T.3: Treatment 3.80 microgram / m3. Nine replicates of each treatment were performed. The analysis was performed from 2 points of view: macroscopic and microscopic. In the macroscopic study it was concluded that the plant decreases its uptake of CO2, since the pollutant affects the development of biomass. Represented in stem height, dry weight and number of leaves. According to the results, the development of biomass is inversely proportional to the concentration of O3. Microscopic analysis revealed that O3 affects stomatal conductance, causing the plant to decrease stomatal opening as a mechanism to prevent further pollutant ingress but at the same time decreases its ability to capture CO2. In addition, because of the oxidative stress generated by the reactive oxygen species (ROS), an ionic imbalance occurs. It affects the permeability of membranes, cell wall degradation and cell death, seen superficially as necrotic spots. The amount of CO2 captured by each treatment was evaluated by electrochemical sensors. Where Treatment 1, is the one that assimilated greater amount of carbon, which justifies a greater development of biomass. Another aspect that justifies a better uptake in comparison to the other treatments is due to the fact that the Treatment 1 did not suffer or suffered in minimal proportions of oxidative stress. Finally, a Spearman analysis was performed to analyze the above-mentioned correlations of the results obtained. The most relevant data was a value equal to -1 in the correlation index, between the concentration of O3 and the amount of CO2 captured. This determines a linearly and inversely proportional influence between the two factors.